Ações políticas ou estratégias políticas? - Toledo, Ana Graziele Lourenço (2016)
The political market is one in which buyers and suppliers negotiate public policies in the similar way to what happens in economic markets: using political strategies. Are notable advances the literature to discuss the effectiveness of these strategies and their relationship to the performance of companies that use them. However, the development of the structure and attractiveness of the political market is still incipient, especially, to explain if the political strategies have the same nature as the market strategies: they represent the company's position in the political market (CAVES; Porter, 1977; Porter, 1980b; HILLMAN; Keim, 1995; HILLMAN; HITT, 1999; BONARDI; HILLMAN; KEIM, 2005). Thus, the objective of this study is to analyze the nature of the actions taken by companies in order to find out if these actions are configured as actual strategies. For this, we used an experimental methodology that modeled the light of game theory, tested determining causal relationships positioning companies in political markets. These relationships were based on the concepts of mobility barriers and isolation mechanisms and were observed in relation to the boss of the political issue and organizational routines. The variables were tested in two different experimental treatments in which subjects were students of the Management degree course, which randomly composed the experimental groups. The results of the experimental sessions showed the existence of positioning of the companies in relation to political strategies according to two variables tested: companies do not change the political strategy in the presence of established organizational routines nor do when there is political issue salience. These findings allow us to advance the discussion of the structure and attractiveness of political markets since proved that even in markets with outcome not differentiated as public policy, companies seek to model and protect unique strategies in the search for better performance.